Laboratory flume experiments for detection and quantification of subsurface particle transport in steep-slope vineyards - Kögler Laura; Ruby Andreas; Iserloh Thomas; Seeger Manuel; Ries Johannes B. (Journal of Hydrology and Hydromechanics, 2025)
Coarse-grained vineyard soils like in the Moselle valley, Germany, can be highly vulnerable to soil erosion. This is due to the non-sustainable soil management using heavy machinery and eliminating the vegetation cover on steep slopes. Through the particular combination of compacted subsoil and topsoil loosened by tillage, the vineyard experiences subsurface runoff after rainfall events. There is a knowledge gap concerning the identification and quantification of transported soil particles in the aforementioned subsurface runoff, as these processes are difficult to accurately measure under field conditions compared to surface runoff. In this paper, an experimental laboratory setup is presented including a newly developed sediment trap to measure and quantify the transport of fine soil particles in subsurface flow. The study showed substantial differences based on the water application method. Nevertheless, the first results show a subsurface sediment discharge of 1 g l−1 on average and 6–8 g l−1 immediately after heavy soil disturbance (simulated tillage). It is highly recommended to conduct further experiments using the method that corresponds most closely to natural processes, the combined method of overflow and sprinkler, as well as installing the sediment trap in a vineyard to validate the findings. If the values can be confirmed, subsurface runoff is a significant contributor to the total soil erosion process and, compared to literature, is responsible for up to 50% of soil erosion in vineyards.